Innovating musical composition through urban noise: A case study in experimental sound - Gilang Rahdianando; Faza Sadikin Permana (Universitas Pendidikan Indonesia, 2022)
The journey from concept to finished product is fascinating and intricate. It begins with a spark of inspiration, an idea that ignites the creative fire within. This concept serves as the foundation upon which the entire project is built. This research used a qualitative method with a case study approach. This research uses two types of data, including audio data of musical compositions and literature sources from articles and journals. The first step is to collect audio samples. This involves scouring libraries, recording sessions, and creating custom sounds to fit the project's vision. Each sample is carefully chosen for its timbre, texture, and emotional impact, which adds depth and richness to the final composition. The steps used are (1) audio data collection; (2) audio editing; (3) composing has four themes: exposition, development, recapitulation, and experimental; and (4) mixing and mastering, for blending all the elements of the track to create a polished and professional sound, and prepares the final blend for distribution, ensuring it sounds great on all playback systems. This involves applying EQ, compression, and limiting to maximize the loudness and clarity of the track.